A study of motivational factors and public service employees’ job performance in Kuching, Sarawak / Susana Anak Madu - Madu, Susana (2017)
The civil service is a noteworthy piece of the modem government. It carries out of the activities that influence numerous parts of citizen's lives. In this manner, the society's or public desire toward the public servant in connection with their execution is very high or above average. Since many scholars believe that there is still lack of study regarding motivation factor and public service employees’ job performance, thus the purpose of this research is to discover the factors that determine public servant job performance. On the other hand, the study also to describe the most significant motivation factor(s) on public service employees job performance. The independent variables involved in this research are pay, reward and recognition and work environment while the dependent variable is motivation factor and employees’ job performance. A total of 12 participants among civil servants in public sector within Kuching were participated in the study. Those participants were from federal government and local government. The result found the majority of the participants agreed that pay (ten (10) out of twelve (12) participants said Yes), reward and recognition (eleven (11) out of twelve (12) participant said Yes) and work environment (twelve (12) participant said Yes) that determines public servant job performance. As for most significant factor (s), majority of the participants stated that pays and reward and recognition as the most significant motivation factor(s) on public service employees’ job performance. The main contribution of this research is that it has covering motivation factor and public service employees’ job performance and it focusing more on the Malaysian public sector specifically within Kuching. In addition, the findings may give potential inputs and an insight to organization’s to adopt. Apart from that, it reveals what is the most significant motivation factor(s) on public service employees’ job performance. Suggestions for future research were also provided in this research.